Development Signs in Healthy Toddlers in Different Stages of Toilet Training: Can They Help Define Readiness and Probability of Success? - Jean-Jacques Wyndaele MD, DBMSc, PhD; Nore Kaerts PhD; Michel Wyndaele MD, PhD; Alexandra Vermandel MPT, PhD (Global Pediatric Health, 2020)
There is much uncertainty about when to start toilet training. Age cannot be a strict stand-alone criterion, as every child has its own pace of development. We observed toilet training (TT) related development signs (DS) in healthy toddlers and determined which can help to define the proper time to start TT and to predict success. The study group consisted of 269 healthy children, in different stages of TT: not started, during, and after completion. Sitting stable, picking up small objects, and spontaneously putting objects in containers were present in all children and had no predictive value. All other DS were significantly more present in those who had started and became more prevalent during completion of TT. Age had a significant association with 13/15 DS. Understanding and following instructions, and having a broader vocabulary were significantly more present when TT had been started. Dry during midday nap reached no significance.